Revealing the role of increased SK3 expression in sulfonylurea resistance triggered by prolonged exposure - Jung Gyu Park; Minseok Kim; Sungje Yoo; Sun Wook Hwang; Jongsoo Mok; Joonghoon Park; Keon Wook Kang (Nutrition & Diabetes)
Abstract Background Sulfonylureas have long been utilized in the management of type-2 diabetes mellitus (T2DM) due to their insulin-secretagogue properties. However, their clinical efficacy is hindered by the risk of severe hypoglycemia and secondary sulfonylurea failure. While the mechanisms underlying sulfonylurea-induced hypoglycemia are well-documented, the precise factors contributing to sulfonylurea resistance (SR) remain poorly understood. This study aims to elucidate the molecular basis of SR in insulinoma cells and an animal model. Methods INS-1E, rat insulinoma cells, were exposed to 10 μM glibenclamide for 7 days to induce sulfonylurea resistance (SR). Sprague-Dawley (SD) rats were fed a diet containing 0.01% glibenclamide for 3 weeks to induce sulfonylurea resistance. Results Insulinoma cells resistant to sulfonylureas exhibited elevated resting membrane potentials compared to sensitive cells. Transcriptome analysis revealed differential expression of genes, notably highlighting the significance of kcnn3 (Potassium Calcium-Activated Channel Subfamily N Member 3) in SR insulinoma cells. Western blot analysis confirmed the upregulation of SK3 protein in correlation with the duration of sulfonylurea exposure. Long-term administration of sulfonylureas in SD rats led to a diminished anti-diabetic response and increased SK3 expression in islets. Conclusion This study elucidates the molecular mechanisms underlying SR, with a specific focus on the overexpression of the SK3 channel in insulinoma cells. These findings enhance our understanding of the challenges associated with prolonged sulfonylurea therapy in the management of T2DM.